Analysis of Standard Error of Measurement (SEM) of 2019 West African Senior School Certificate Examination Multiple-Choice Objective Tests in Economics - D, Adewuni,; Y. Taiwo, Busari, (Kashere Journal of Education, 2021)
This study analyzed the Standard Error of Measurement (SEM) of 2019 May/June West African Senior School Certificate Examination Multiple-choice Objective Tests in Economics at three different confidence Interval (CI). A quantitative research design of the descriptive type was adopted for the study. The sample of the study was Three hundred and Two (302) Senior Secondary School Three (SSS.3) students that offered Economics selected from twelve (12) schools in the three senatorial districts in Osun State, Nigeria and Multi-stage sampling technique was adopted in this study. 2019 May/June and Nov/Dec (GCE/WASSCE) Multiple-Choice Objective Tests in Economics were adopted as instruments for the study. Data collected were analyzed using Descriptive statistics. The findings of this study revealed that the performance of students in WASSCE May/June Economics Multiple choice objective test of 2019 flagged the SEM of 4 (+ or - 4). Also, the performance of students in 2019 GCE WASSCE Economics Multiple-choice objective test flagged the SEM of 12 (+ or - 12) both at 68% confidence interval. It was concluded that 2019 May/June WASSCE Economics Multiple-choice objective test is more precise, reliable and correct than 2019 GCE WASSCE Economics Multiple-choice objective test at all the confidence intervals. The study recommended that educators should consider the magnitude of SEMs for students across the achievement distribution. It was also recommended that test practitioners should adopted classical Test Theory (CTT) in test scoring and test precision.